2015
DOI: 10.1179/1743132815y.0000000072
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry in brain death: differences in pupillary diameter between paediatric and adult subjects

Abstract: This is the first study in the literature objectively evaluating pupil sizes in infants, children and adults diagnosed with brain death. We observed variation between observed pupil size and that expected based on brain death determination guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…Damage to several levels of the pupil control centers occurs as a result for BD. The diameter of a denervated pupil, without any parasympathetic and sympathetic control, remains approximately 3-7 mm dilated, according to various works in the literature [7,8]. At the onset of BD, together with nuclei necrosis of the oculomotor nerve, parasympathetic impulsion always wanes, leaving the pupil dilated at least 3-4 mm.…”
Section: Discussionmentioning
confidence: 95%
“…Damage to several levels of the pupil control centers occurs as a result for BD. The diameter of a denervated pupil, without any parasympathetic and sympathetic control, remains approximately 3-7 mm dilated, according to various works in the literature [7,8]. At the onset of BD, together with nuclei necrosis of the oculomotor nerve, parasympathetic impulsion always wanes, leaving the pupil dilated at least 3-4 mm.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have demonstrated that it outperforms manual examination for adults in the critical care setting (87,88). Data regarding the efficacy of pupillometry in children is limited (89). Because absence of the pupillary light reflex is a requisite for brain death, pupillometers may help to prevent false positive diagnoses if more data arises to support its reliability.…”
Section: Brain Death and Evolving Technologiesmentioning
confidence: 99%
“…Pupilla muayenesi birçok oküler ve nörolojik hastalığın, serebral ve orbital travmanın ve ilaç toksisitesinin teşhis ve takibinde büyük önem taşımaktadır. [11][12][13] Ancak, pupillar parametrelerin subjektif analizi, gözlemciler arası değişkenlikten dolayı önemli ölçüde etkilenebilmektedir. Objektif pupilla değerlendirmesi için kullanılan pupillometri cihazları, kontrollü ortam aydınlatması koşullarında ışığa verilen pupil yanıtlarının otomatik, çoklu, kantitatif ölçümlerini elde edebilmektedir.…”
Section: Gereç Ve Yöntemlerunclassified